PTU-068 Response to antiviral therapy in genotype 3 hepatitis C—cirrhosis and diabetes but not ethnicity reduce response rates. (23rd September 2015) - Shoeb, D; Rowe, I; Brown, A; Marley, R; Freshwater, D; Moreea, S; Mutimer, D; Foster, G
Abstract : Introduction: The impact of ethnic background on response to antiviral therapy in patients with genotype 3 chronic hepatitis C infection remains unclear. Methods: We performed a large retrospective analysis of 535 patients (268 Caucasian, 267 South Asian) treated with pegylated interferon and ribavirin at four UK centres. Results: At baseline age, sex and proportions with cirrhosis were compared between the South Asians and Caucasians and cirrhosis was the only factor more common in people from South Asia 83/267(31%) vs Caucasian 56/268 (20.8%) and this was statistically significant (p=<0.05). The overall sustained virological response rate (SVR) was 77.6%. In univariate analysis, age, diabetes, cirrhosis and need for dose reduction were associated with treatment failure. Ethnicity (Caucasian vs South Asian) did not affect SVR (proportions achieving SVR were 210/268=78.3%% in Caucasians and 209/267=78.2% in South Asians). In a multivariable analysis cirrhosis and presence of diabetes were the only factors significantly associated with a reduction in the proportion who achieved an SVR. Treatment failure was due to relapse in the majority of patients (70/535 patients relapsed (13.08%) while 46/535 (8.59%) had a breakthrough or no response. Relapse was inevitable in patients who did not achieve an early virological response (all 32 patients without an EVR relapsed) and was more common in those who did not have a rapid virological response (relapse occurred in18/96–18.7% who did not have an RVR compared to 8/153, 5.2% who did have a RVR, p=<0.001). Conclusion: The SVR in patients with genotype 3 chronic HCV infection is similar in patients from South Asia and Caucasians. The presence of cirrhosis significantly reduces the response to therapy and relapse is the most common mode of treatment failure.